The Nuts and Bolts of Baseline Setting : Why, What and How? - Partnership for Market Readiness (World Bank, Washington, DC, 2015)
This document provides an overview of baseline setting for greenhouse gas (GHG) crediting mechanisms. The first section briefly explains the general purpose and objectives of setting a crediting mechanism baseline. The second section summarizes key policy considerations in defining and setting baselines. The final section covers important technical elements of baselines and provides an overview of various methods that can be used to estimate baseline emissions. The main purpose of this technical note is to examine key issues for baseline setting in the context of scaled-up crediting mechanisms. Many of the technical and policy considerations presented here, however, are relevant to existing project-based crediting mechanisms as well, and the discussion takes into account concepts developed and experience gained under these mechanisms. In addition, most of the concepts and examples presented here are relevant to setting baselines in the energy and industry sectors. Where relevant, however, examples from other sectors, including forestry and land-use, are used to illustrate important ideas.